Impact of Virtual Reality Relaxation Training on Somatic Anxiety and Coping Strategies - Ivanyan , Arusyak (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to evaluate the effectiveness of an eight-session Virtual Reality Relaxation Training (VRRT) program on reducing somatic anxiety and improving coping strategies in young adults. A randomized controlled trial was conducted with 30 participants from Armenia, randomly assigned to either an experimental group (n = 15) receiving VRRT or a control group (n = 15) placed on a waitlist. The intervention consisted of weekly 60-minute sessions over eight weeks, involving immersive virtual environments integrated with guided breathing, progressive muscle relaxation, mindfulness, and visualization. Somatic anxiety was measured using the Beck Anxiety Inventory (BAI), and coping strategies were assessed with the Coping Inventory for Stressful Situations (CISS). Assessments were conducted at three time points: pretest, posttest, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests via SPSS-27. Repeated measures ANOVA revealed significant group × time interaction effects for both somatic anxiety (F = 23.19, p < .001, η² = .462) and coping strategies (F = 19.66, p < .001, η² = .412). Bonferroni post-hoc tests indicated that the experimental group showed a significant reduction in somatic anxiety from pretest to posttest (p < .001), which was sustained at follow-up. Likewise, significant improvements in coping strategies were observed in the experimental group (p < .001), with no significant change in the control group across time. The findings support the effectiveness of Virtual Reality Relaxation Training in reducing somatic anxiety and enhancing coping strategies, with sustained benefits observed up to five months post-intervention. VRRT offers a promising, immersive approach for anxiety management and resilience training among young adults.